Modified Jobe Versus Docking Technique for Elbow Ulnar Collateral Ligament Reconstruction: A Systematic Review and Meta-analysis of Clinical Outcomes. Issue 1 (January 2021) - Looney, Austin M.; Wang, David X.; Conroy, Christine M.; Israel, Jake E.; Bodendorfer, Blake M.; Fryar, Caroline M.; Pianka, Mark A.; Fackler, Nathan P.; Ciccotti, Michael G.; Chang, Edward S.
Background: The modified Jobe and docking techniques are the most common techniques used for elbow ulnar collateral ligament (UCL) reconstruction. Previous systematic reviews have suggested that the docking technique results in superior outcomes as compared with the Jobe (figure-of-8) technique. However, these included results from earlier studies in which the flexor-pronator mass (FPM) was detached and an obligatory submuscular ulnar nerve transposition was performed. Purpose/Hypothesis: The purpose was to compare the outcomes and return-to-play (RTP) time between the docking and figure-of-8 techniques for UCL reconstruction. We hypothesized that there would be no significant difference in the proportion of excellent outcomes between techniques when the FPM was preserved and no obligatory submuscular ulnar nerve transposition was performed. We also hypothesized that there would be no significant difference in RTP time between techniques. Study Design: Systematic review and meta-analysis. Methods: This study was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. In the primary analysis, techniques were compared in random effects models by using the restricted maximum likelihood method, with weighted effect sizes calculated as the Freeman-Tukey double-arcsine transformed proportion of excellent outcomes for variance stabilization and with summary effects estimated from the inverse double-arcsine transformation per the harmonic mean of the sample sizes. Mean RTP times for techniques were compared in a separate model. Results: There were 21 eligible articles identified, with results for 1842 UCL reconstructions (n = 320, docking; n = 1466, figure-of-8). Without controlling for the effects of flexor-pronator detachment and submuscular ulnar nerve transposition, a significantly larger proportion of excellent outcomes was observed with docking reconstruction (86.58%; 95% CI, 80.42%-91.85%) than with figure-of-8 reconstruction (76.76%; 95% CI, 69.65%-83.25%; P = .031); however, there was no significant difference between techniques when controlling for FPM preservation or detachment with submuscular nerve transposition ( P = .139). There was no significant difference between techniques in time to return to sports ( P = .729), although no reconstructions with FPM detachment and submuscular ulnar nerve transposition were available for RTP time analysis. Conclusion: There was no significant difference in the proportion of excellent Conway Scale outcomes or RTP time between the docking and modified Jobe techniques for UCL reconstruction when the FPM was preserved and routine submuscular ulnar nerve transposition was not performed.